2020
DOI: 10.1016/j.ajic.2020.06.203
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a portable negative pressure hood with HEPA filtration to protect health care workers treating patients with transmissible respiratory infections

Abstract: Background: To mitigate potential exposure of healthcare workers (HCWs) to SARS-CoV-2 via aerosol routes, we have developed a portable hood which not only creates a barrier between HCW and patient, but also utilizes negative pressure with filtration of aerosols by a high-efficiency particulate air filter. Material and Methods: The hood has iris-port openings for access to the patient, and an opening large enough for a patient's head and upper torso. The top of the hood is a high-efficiency particulate air filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Particles retained within the tent fell within the size range of airborne particles of probable respiratory origin shown to contain SARS-CoV-2 RNA in clinical studies, and in particular those < 5 μm in diameter shown to carry the highest coronavirus titres [ 5 , 31 ]. Although this study was not conducted with infectious particles or human subjects, this suggests that the Demister 2000, like other portable isolation devices employing filtered extraction [ 32 ], would prevent the dispersal of respiratory viruses such as SARS-CoV-2 from aerosols generated from infected patients. By effectively expanding isolation capacity without building or structural alterations, these devices have potential to increase treatment capacity during respiratory pandemics whilst protecting healthcare staff and patients from infection.…”
Section: Discussionmentioning
confidence: 99%
“…Particles retained within the tent fell within the size range of airborne particles of probable respiratory origin shown to contain SARS-CoV-2 RNA in clinical studies, and in particular those < 5 μm in diameter shown to carry the highest coronavirus titres [ 5 , 31 ]. Although this study was not conducted with infectious particles or human subjects, this suggests that the Demister 2000, like other portable isolation devices employing filtered extraction [ 32 ], would prevent the dispersal of respiratory viruses such as SARS-CoV-2 from aerosols generated from infected patients. By effectively expanding isolation capacity without building or structural alterations, these devices have potential to increase treatment capacity during respiratory pandemics whilst protecting healthcare staff and patients from infection.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 These enclosures utilized a suction device to generate negative pressure and HEPA filters to help prevent the spread of aerosolized particles, with the openings either uncovered or covered with rubber septum. 18,19 Phu et al reported a 99% particle reduction in the 0.5 to 5 µm range, which is slightly higher than the 93-97% reduction reported here without suction. This is likely due to our particle measurements extending down to smaller sizes (to 0.01 µm), because these smaller particles can more easily escape the enclosure.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted November 24, 2020. ; https://doi.org/10.1101/2020.11.23.20237255 doi: medRxiv preprint Several approaches have recently been developed to help protect healthcare providers during these procedures, including placing plastic barriers or hoods over the patient in an effort to contain produced aerosols. 16,18,19 A limitation is that the enclosure must have sizable openings in its side walls to allow the introduction of medical equipment and provide the healthcare worker's hands access to the patient. These holes have been found to funnel the aerosol that escapes from the enclosure.…”
Section: Background/introductionmentioning
confidence: 99%
“…as simple as plastic sheeting Matava, Yu and Denning (2020) or rigid boxes), methods using enclosures combined with a degree of suction, (e.g. as described by Perella, Tabarra, Hataysal, Pournasr, and Renfrew (2021) and Phu et al (2020) ), and methods which may include some shield or barrier, but which primarily rely on capture of aerosol by suction. An example of the latter is decribed in the model study reported by Matava et al (2020) , in which the capture performance is studied for a conical nozzle placed 25–35 cm above the mouth of a mannikin.…”
Section: Design Requirementsmentioning
confidence: 99%